2016
DOI: 10.21873/invivo.11000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Canine Cutaneous Peripheral Nerve Sheath Tumors: A Drawback in the Diagnosis Refinement

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…These data may be explained by the high proliferative rate of this tumour . This is also confirmed by the elevated expression of Ki‐67 protein, a widely used proliferation marker, in our COM cases as compared to other canine tumours such as mast cell tumours, indolent lymphoma, gastrointestinal stromal tumours, mammary tumours, peripheral nerve sheath tumours and gliomas …”
Section: Discussionsupporting
confidence: 83%
“…These data may be explained by the high proliferative rate of this tumour . This is also confirmed by the elevated expression of Ki‐67 protein, a widely used proliferation marker, in our COM cases as compared to other canine tumours such as mast cell tumours, indolent lymphoma, gastrointestinal stromal tumours, mammary tumours, peripheral nerve sheath tumours and gliomas …”
Section: Discussionsupporting
confidence: 83%
“…To date, there is no immunohistochemical marker that is expressed exclusively by PNSTs [20]. The immunohistochemical analysis of the 17 tumor samples in this study showed positivity for S-100 protein and glial fi brillary acidic protein in 13 cases.…”
Section: Discussionmentioning
confidence: 49%
“…Since the expression of S-100 protein may be present in some other tumors, even in those of non-neuronal origin (such as synovial sarcomas, leiomyosarcomas, and rhabdomyosarcomas), it should not be considered as defi nite proof of PNST [3,21]. However, the lack of S-100 protein expression is described in some cases of canine MPNSTs [3,19,20]. It is explained by the fact that MPNSTs consist of several cell types and S-100 protein expression will be strong only in tumors consisting predominantly of Schwann cells and a smaller number of perineural cells and fi broblasts [22].…”
Section: Discussionmentioning
confidence: 99%
“…The survival time was shorter in human patients having Ki-67 index exceeding 25%. In canine cutaneous PNSTs, the expression of Ki-67 was ranged 0.6%-80.9%, showing higher index in MPNSTs (35.4+27.8%) than those in PMSTs (16.3+17%) [15]. The expression of Ki-67 in primary and metastatic lesion in the case were 34.6% and 26.5%, respectively, both of which were greater than 25%, implying that the MPNST in the case was highly aggressive.…”
mentioning
confidence: 83%
“…There are some variations, increasing (24%), stable (66%), and decreasing (10%) of Ki-67 in metastatic lesion in human neuroendocrine tumors [7]. Since Ki-67 can be used for grading or predicting prognosis in human PNSTs [18][19][20] and in canine PNSTs [15], Ki-67 is an available marker for physiological states and prognosis in MPNSTs. To our knowledge, this is the first report in humans or animals on the invasion of MPNSTs into the abdominal cavity from the vertebral canal through the nerve root.…”
mentioning
confidence: 99%